Predator-Friendly Beef Certification as an Economic Strategy to Promote Coexistence Between Ranchers and Wolves - Bogezi, Carol; van Eeden, Lily M.; Wirsing, Aaron; Marzluff, John (Frontiers in Ecology and Evolution, 2019)
Real and perceived economic losses are key factors driving negative attitudes and lack of tolerance toward carnivores. Alleviating economic losses through compensation and market-based strategies is one tool for addressing negative human-carnivore interactions. Despite general support among the public for market-based economic incentives to improve coexistence with predators, products marketed as ‘predator-friendly’ are rare in mainstream markets. We explored stakeholders’ perspectives on certification of predator-friendly beef as a market-based economic incentive to enable ranchers to better coexist with gray wolves (Canis lupus) in Washington state, USA. We conducted semi-structured interviews (N = 104) and explored narratives using grounded theory to understand the perspectives of stakeholders involved in the cattle-wolf relationship, including ranchers, wildlife agency personnel, environmental non-government organization employees, beef industry workers, and politicians. Both economic and social factors motivated and constrained ranchers to participate in a program creating a predator-friendly beef label. Ranchers largely perceived marketing their products as predator-friendly to be more of a public outreach opportunity than a new source of income. Most stakeholders perceived an economic opportunity for predator-friendly beef facilitated by existing pro-environmental markets and existence of a private beef processing plant. Based on these results, we propose a design for effectively implementing a predator-friendly beef market. We recommend focusing on the type and objective of the rancher, ensuring local access to beef processing facilities to process small volumes of custom beef, developing a product brand that is favored by ranchers and beef processors, considering viable product pricing , and developing a regulatory process for a potential predator-friendly beef label on the mainstream market.